L’integrazione delle tecnologie nell’educazione linguistica come obiettivo della preparazione degli insegnanti - Torsani, Simone (Educazione Linguistica Language Education, 2015)
Integration of IT into classroom language teaching has ever since been the goal of CALL education. This article sets out to discover how teachers acquire integration skills during CALL training programmes. A case study approach, that included interviews with the trainee teachers and observation of their dissertations, was employed to appreciate how four in-service teachers reacted to three different learning activities and how they perceived the development of their CALL expertise. The study highlighted the importance of project work as it can provide teachers with a first-hand experience of the diverse factors that influence integration.